Análisis epidemiológico de la incidencia de enfermedades autoinmunes, tromboembólicas y neurológicas en Colombia, en mujeres vacunadas con la vacuna cuadrivalente contra el virus del papiloma humano del 2012 al 2018 (2020)
Despite the high incidence of human papillomavirus (HPV), the diseases it causes (including cervical cancer), the multiple studies that prove the safety of the vaccines developed (Macartney et al., 2013) and the reports of the WHO that recommend the application of the vaccine, there is still some skepticism regarding the safety of the vaccine against the human papillomavirus. Events such as those that occurred in Carmen de Bolívar (Colombia) and Japan in 2014 (Cervantes & Doan, 2018) increased mistrust in the vaccine and led to the suspension of the recommendation to apply it in both countries. Given this context, the present study seeks to present a methodology to estimate the average effect of the quadrivalent HPV vaccine on the incidence of autoimmune, thromboembolic, and neurological diseases in Colombia in vaccinated women from 2012 to 2018, in order to assess whether there is a positive and significant causal relationship.